The Linguistic Dimensions of the Madrasah Arabic Curriculum in Vygotsky’s Constructivist Perspective - Khalifaturrosyidah Handayani; Faisal Mahmoud Adam; Zakiyah Arifa (Dzil Majaz: Journal of Arabic Literature, 2026)
The current Arabic language curriculum in Madrasahs has been designed in alignment with the Kurikulum Merdeka, which emphasizes competency-based learning, collaboration, and problem-solving. Vygotsky’s social constructivist theory is believed to address these challenges effectively, as it highlights the importance of social interaction, scaffolding, and context-based learning. This study aims to describe the implementation of the Arabic language curriculum from the perspective of Vygotsky’s constructivist theory at Madrasah Aliyah Husnul Khatimah and its impact on students’ learning motivation. The research employed a qualitative case study approach with data collected through semi-structured interviews, participatory observation, and documentation study. Data analysis followed the Miles, Huberman, and Saldana model, consisting of data condensation, data display, and conclusion drawing, which were verified through source and technique triangulation. The implementation of the Arabic language curriculum from the perspective of Vygotsky’s constructivist theory has brought significant changes to the learning process. Teachers act as facilitators who guide students through collaborative activities such as discussions, language games, and group work. The gradual application of scaffolding enhances students’ independence and confidence in using Arabic. Social interaction among students strengthens intrinsic motivation, as they feel valued and actively engaged in the learning process. Overall, the implementation of the Arabic language curriculum through Vygotsky’s constructivist perspective has proven to have a positive impact on students’ learning motivation and language skills. This approach aligns well with the Kurikulum Merdeka, which emphasizes active, reflective, and student-centered learning.